Persepsi Kepala Sekolah terhadap Etika dan Kinerja Pengawas Sekolah di MIS Al-Ishlah Kabupaten Bekasi - Sania Vikasari; Astuti Darmiyanti (Journal on Education, 2023)
Education is a very important component for a country to highlight its existence as a nation with integrity and be able to compete with other developed countries. The supervisor is an organization that is fully committed to improving the quality of education and its role in the education system is very important. The school supervisor also acts as a supervisor at the school he supervises, both in academic and managerial terms. The purpose of this study was to determine the ethics and performance of school supervisors in improving the quality of education seen from the perceptions of the principal at MIS Al-Ishlah, Bekasi Regency. This research can be useful for providing scientific information to educators. When this research was conducted on December 3, 2022 at the MIS Al-Ishlah in Bekasi Regency West Java, using a qualitative descriptive research method. Researchers collect data through observation, interviews and documentation. From the results of the study, the school supervisor correctly carried out his duties as a school supervisor at MIS Al-Ishlah. By supporting, fostering school principal programs, supervising or monitoring, conducting assessments and up to program evaluations. In supervision, the responsibility is almost entirely in the hands of the school principal, however, the supervisor's role is inseparable from always guiding and monitoring any developments in the school.